Syncretism on Catholic Symbols in The Invulnerability Rituals in West Borneo - Arius Arifman Halawa; Lukas Ahen; Cenderato Cenderato (Al-Albab, 2022)
Catholic churches highly appreciate human customs and cultures to recognize ways for humans to express and develop their humanity. They often include elements of art and culture in liturgical symbols as a form of expressing faith in God. Many liturgical songs use ethnic songs, images and building form with certain traditional and cultural motifs. This study aims at examining the use of Catholic religious symbols by a group of Catholic Youths in West Borneo in practicing invulnerability. The practice actually experienced a mix that creates a religious syncretism and is contrary to the Catholic faith. The work focuses on the use of Catholic religious symbols in the preservation of Dayak customs in West Borneo, the view of the leadership of the Catholic Church on the use of Catholic religious symbols to preservate Dayak customs in West Borneo. This study used a qualitative method with the instruments of Interview and Questionnaire. Some people used church symbols in invulnerability rituals, especially during Dayak cultural activities, such as the cross symbol, the Rosary, statues of Jesus/Mother Mary in various sizes. In addition, they also used Catholic prayers to open with the sign of the cross, the Lord’s Prayer, the Hail Mary and the Prayer I Believe. From the church’s perspective, invulnerability knowledge is local wisdom that needs to be apreciated. However, it is contrary to the teachings of the Church and is inappropriate to the intent and purpose of their existence.